Adrenocortical pheochromocytoma diagnosed during pregnancy: a case report - Xiaoteng Qiang; Yin Li; Qing Bai; Jing Huang; Xuemei Ma; Weiwei Wang (BMC, 2023)
Abstract This paper reports a rare case of adrenocortical carcinoma (ACC) diagnosed during pregnancy presenting with gestational hypertension. Hypertensive disorders in pregnancy should receive enough attention to identify and exclude the possibility of adrenal diseases, thereby making a timely diagnosis and active treatment.